Origin of the aa. metacarpeae palmares profundae medialis and lateralis in througlibred horses (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1972)
The AA. observed the origin of the arteriae metacarpeae palmares profundae medialis and lateralis in 50 thoracic limbs, concerning to 25 thoroughbred horses (males and females). They described the following dispositions: a) the a. metacarpeae palmaris profundae medialis arises from the a. mediana, before the origin of the a.m.p.p. lateralis — 29 cases (58.0% ± 7.0) ; b) the a.m.p.p. medialis arises from the a. mediana, after the origin of the a.m.p.p lateralis — 15 cases (30.0% ± 6.5); c) the aa.m.p.p. medialis and lateralis arise from the a. mediana at the same level — 5 cases (10.0% ± 4,2); d) the aa.m.p.p medialis and lateralis arise from the a. mediana by a common stem — 1 case (2.0% ± 2.0).